Are current approaches for measuring access to clean water and sanitation inclusive of people with disabilities? Comparison of individual- and household-level access between people with and without disabilities in the Tanahun district of Nepal - Banks, Lena Morgon (PLoS One, 2019)
BACKGROUND: The critical importance of safe and affordable access to water, sanitation and hygiene (WASH) is highlighted in Goal 6 of the Sustainable Development Goals, which seeks to achieve universal and equitable access for all by 2030. However, people with disabilities–who comprise 15% of the global population–frequently face difficulties meeting their WASH needs. Unmet WASH needs amongst people with disabilities may not be captured through current approaches to tracking progress towards Goal 6, which focus on household- rather than individual-level access. OBJECTIVE: To evaluate access to safe water, sanitation and hygiene (WASH), at the individual- and household-level, amongst people with disabilities in the Tanahun district of Nepal. METHODS: A population-based survey of disability was conducted from August-October 2016 to evaluate access to improved water and sanitation facilities between households with members with disabilities (n = 198) and those without (n = 1,265) in the Tanahun district of Nepal. A nested case-control then compared individual-level access between cases aged 15 and above with disabilities (n = 192) and age-sex-location matched controls without disabilities (n = 189), using the newly developed 21-item “Quality of WASH Access” questionnaire. Multivariate regression was used to compare household- and individual-level indicators between people and households with and without disabilities. In-depth interviews with 18 people with disabilities and their caregivers was conducted to assess the acceptability and appropriateness of the “Quality of WASH Access” questionnaire. FINDINGS: There were no significant differences between households with and without members with disabilities in access to an improved sanitation facility or water source. However, at the individual-level, people with disabilities experienced significantly greater difficulties accessing water, sanitation and hygiene compared to people without disabilities (p<0.001 for all three scores). Amongst people with disabilities, water difficulty scores were associated with having a physical impairment and greater disability severity; sanitation difficulty scores were associated with lower socioeconomic status and physical or self-care limitations; and hygiene difficulty scores were positively associated with self-care limitations and lower socioeconomic status, and inversely associated with hearing impairments. Qualitative research found the “Quality of WASH Access” questionnaire was well understood by participants and captured many of the challenges they faced. Additional challenges not covered by the tool included: (1) time spent on WASH, (2) consistency of access, (3) sufficiency of access, and (4) dignity of access. CONCLUSION: People with disabilities face substantial challenges to meeting their WASH needs, particularly in using services autonomously, consistently, hygienically, with dignity and privacy, and without pain or fear of abuse. These challenges are not captured through household-level data, and so individual-level WASH access are needed to monitor progress towards universal WASH access. The Quality of WASH Access questionnaire may provide a useful data collection tool.